2012
DOI: 10.21301/eap.v7i4.14
|View full text |Cite
|
Sign up to set email alerts
|

Observation of “Traditional” Agriculture in Kastamonu, Turkey In Relation to the Evidence of Crop Husbandry at Neolithic Çatalhöyük, Central Anatolia

Abstract: In order to better understand how plants were procured and consumed at Neolithic Çatalhöyük, the site’s archaeobotany team examined some of the existing ethnographic examples of “traditional” (non-mechanised) farming in Turkey. The Kastamonu region of the north Turkey is an area where some ’ancient’ wheats (einkorn and emmer) are cultivated in a more or less traditional way and on a small-scale. Fieldwork in this part of Turkey provided first-hand knowledge of some off- and on-site agricultural activities whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…This core set of staple foods confirms that these early crops were used in combination at the household level, reflecting cultivation of annual seed crops alongside gathering of wild resources. While some of these assemblages can be inferred to have come from the use of animal dung as fuel, others are more directly related to the waste from human activities such as crop processing waste (Bogaard et al 2013 ; Filipović 2014 ). Fairbairn et al ( 2005 ) also demonstrated that residues raked out of fireplaces are the most concentrated deposits of charred plant material produced through routine practices; these primary deposits were subsequently re-used and deposited as secondary contexts in middens and as tertiary contexts in building fills and construction material.…”
Section: Neolithic çAtalhöyük Plant Subsistencementioning
confidence: 99%
“…This core set of staple foods confirms that these early crops were used in combination at the household level, reflecting cultivation of annual seed crops alongside gathering of wild resources. While some of these assemblages can be inferred to have come from the use of animal dung as fuel, others are more directly related to the waste from human activities such as crop processing waste (Bogaard et al 2013 ; Filipović 2014 ). Fairbairn et al ( 2005 ) also demonstrated that residues raked out of fireplaces are the most concentrated deposits of charred plant material produced through routine practices; these primary deposits were subsequently re-used and deposited as secondary contexts in middens and as tertiary contexts in building fills and construction material.…”
Section: Neolithic çAtalhöyük Plant Subsistencementioning
confidence: 99%
“…Many of the dominant taxa in these samples grow in saline habitats ( Aeluropus, B. maritimus ) or marshy areas (rushes), and others have small or hard-coated seeds (small-seeded legumes), Chenopodiaceae, Brassicaceae, Helianthemum ( ledifolium ) that survive passage through the ruminant digestive system (Miller and Smart 1984; Charles 1996; Wallace and Charles 2013). These, and several less dominant small-seeded taxa ( Sporobolus (saline habitats), Chenopodium chenopodioides, Juncus (marshy areas), Alopecurus, Artemisia annua ), are suggestive of grazing habitats, and the burning of dung fuel has been suggested as a major contributor of the plant remains found in these deposits (Bogaard et al 2013; Filipović 2014). The Çatalhöyük samples are not unique in this respect; for example, Epipalaeolithic samples from Abu Hureyra, including a large mixed sample, which plots with the large Çatalhöyük midden samples, are also composed of taxa consistent with derivation from dung (Miller 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of elucidating crop-growing conditions and agricultural management, arable weeds are a prime piece of evidence (e.g. Bogaard, 2004, 2010; Filipović, 2014; Jacomet et al, 1989: 180–189; Jones, 2002; Jones et al, 1999; Kreuz, 2012; Kreuz and Schäfer, 2011; Maier and Vogt, 2001: 86–100; Wasylikowa, 1981). In this study, the wild taxa were identified as potential weeds (cf.…”
Section: Methodsmentioning
confidence: 99%